Literature review of the systematics, biology and role in malaria transmission of species in the Afrotropical Anopheles subgenus Anopheles (Diptera: Culicidae) - Coetzee, Maureen (Zootaxa, 2022)
It has been 34 years since the last update of the subgenus Anopheles Meigen, 1818 in the Afrotropical Region. Eleven species occur in the region, and of these, eight occur only on the African continent, two in both Africa and Madagascar, and one exclusively in Madagascar. Three species are implicated in the transmission of malarial parasites in localised areas: An. coustani Laveran, 1900 (Cameroon, Central African Republic, Democratic Republic of the Congo, Kenya, Madagascar, Tanzania and Zambia), An. paludis Theobald, 1900 (Cameroon, Democratic Republic of the Congo) and An. ziemanni Grünberg, 1902 (Cameroon, Chad, Ethiopia and Rwanda). Several arboviruses have been isolated from An. coustani in Kenya, Madagascar and Senegal. Recent molecular studies indicate possible undescribed species within An. coustani that could be resolved with integrated molecular, morphological and cytogenetic methods.